Global Environmental Change - Global Environmental Change (Elsevier, 2026)
Global Environmental Change is a peer-reviewed international journal publishing high quality, theoretically and empirically rigorous articles, which advance knowledge about the human and policy dimensions of global environmental change. The journal interprets global environmental change to mean the outcome of processes that are manifest in localities, but with consequences at multiple spatial, temporal and socio-political scales. The journal is interested in articles which have a significant social science component. These include articles that address the social drivers or consequences of environmental change, or social and policy processes that seek to address problems of environmental change. Topics include, but are not restricted to, the drivers, consequences and management of changes in: biodiversity and ecosystem services, climate, coasts, food systems, land use and land cover, oceans, urban areas, and water resources.
FI 2.38
Q1
Keywords: Earth; Space & Environmental Sciences; Earth Sciences; Ciencias de la Tierra; Acuerdos transformativos; Transformative agreements; Cambio ambiental; Factores sociales; Clima; Suelos; Oceános; Biodiversidad